Competition as a Discovery Procedure in the P ractice of Accounting - Duarte, Edgar (REVISTA PROCESOS DE MERCADO, 2017)
Even though they developed separately as two distinct disciplines, there is a complex relationship between accounting and econom-ics. For example: 1) accounting is a means that makes economic calculation possible; it provides the managers, the investors and lenders (current and potential), and the public in general with in-formation that aids them in assessing the profitability and the ap-propriate use of resources of a business. Although mainly histori-cal, accounting information allows them to form an expectation of future performance and hence it is useful for making economic decisions; 2) economics theorizes on the same ele-ments which ac-counting endeavors to measure; 3) the market for financial report-ing, i.e. for the financial statements and other information dis-closed periodically by companies, which is one of the products of an accounting system, is a market like that of any other good or ser-vice and it is therefore subject to the same economic analysis. Given this complex relation-ship, there are several paths an eco-nomic work on accounting could take. This author will approach his study first by acknowledging that accounting is an evolving institution, one of spontaneous forma-tion that has not yet reached, and probably will never reach, its fi-nal form. Although its form and practice has been subjected to regulation by dif-ferent governments and governmental agencies for centuries, in particular the market for fi-nancial reports of pub-lic companies, that fact does not change its spontaneous character. The author will also argue that competition is underutilized as a discovery procedure in accounting in general and in the prepara-tion of financial reports in particular. As a consequence of govern-ment intervention, better and less expensive ways of serving the consumers of financial reports have not yet been discovered under the current system. As an economist and practicing accountant, this author could be tempted to try to prescribe the form and substance of the finan-cial reports. Although admittedly economics could inform a lot about this, and the author does not deny the importance of those investigations for the marketplace of ideas, one of the main conclu-sions of this essay is that one of the tasks of competition is pre-cisely to discover the characteristics of the goods and services that best serve the consumers and hence, to discover the substance and form of the financial reports that best aid the users for their par-ticular ends. After this introduction, in the second part of this essay, the au-thor will summarize the conceptions that Friedrich A. Hayek de-veloped and that are relevant for his analysis. In the third part, an elaboration of accounting as a language is provided. In the fourth part, a brief summary of the history of accounting, since the spon-taneous emergence of the double entry bookkeeping system in me-dieval Europe until our times, will be presented, along with the origin and alleged justifications of government intervention in ac-counting. In the fifth part, the author will enumerate some of the problems presented by such intervention. In the sixth part, to con-clude this essay, a general prediction of a free market in accounting services will be presented. Financial reporting is a subset of accounting. Usually the same system fulfills several ends such as filling tax statements (tax ac-counting), tracking and allocation of cost elements to different products or services (cost accounting) and the preparation of fi-nancial reports for external users such as current and potential lenders and investors (financial accounting). In this work, the ar-guments are addressed in general to accounting and in particular to financial reporting. When names such as financial reporting, financial reports, financial accounting, external reporting and oth-ers similar are not explicitly mentioned, the arguments should be understood as applying to accounting in general.